Multiple Pulse Amperometry—An Antifouling Approach for Nitrite Determination Using Carbon Fiber Microelectrodes - Douglas P. M. Saraiva; Daniel V. Braga; Bruna Bossard; Mauro Bertotti (Molecules, 2023)
Nitrite is a ubiquitous pollutant in modern society. Developing new strategies for its determination is very important, and electroanalytical methods present outstanding performance on this task. However, the use of bare electrodes is not recommended because of their predisposition to poisoning and passivation. We herein report a procedure to overcome these limitations on carbon fiber microelectrodes through pulsed amperometry. A three-pulse amperometry approach was used to reduce the current decay from 47% (after 20 min under constant potential) to virtually 0%. Repeatability and reproducibility were found to have an RSD lower than 0.5% and 7%, respectively. Tap water and synthetic inorganic saliva samples were fortified with nitrite, and the results obtained with the proposed sensor were in good agreement with the amount added.